KAJIAN SOSIOLINGUSTIK PEMAKAIAN BAHASA MAHASISWA ASING DALAM PEMBELAJARAN BAHASA INDONESIA UNTUK PENUTUR ASING (BIPA) DI UNIVERSITAS SEBELAS MARET - Kundharu Saddhono (Universitas Muhammadiyah Surakarta, 2012)
This study examines the use of languages by foreign students in learning the Indonesian language for foreign speakers (BIPA). Sociolinguistic approach is employed in which in-depth interview is used to elicit the reseach data. Sociolinguistic analysis is conducted by considering the social context of the speech components. The results show that the dominant use of Indonesian language by the learners is the language of instruction acquired in the process of learning the language. English emerges as the language of mediation between teachers and students spoken when they have difficulties in learning. Another language that appears in the language learning is Javanese which is the vernacular of Surakarta. Aspects of Indonesian cultural context should be taught to the learners. A variety of language styles for formal and informal conversation must be understood by foreign students so as to avoid errors in language usage.